Cardiovascular Medication Use and Long‐Term Outcomes of First Nations and Non–First Nations Patients Following Diagnostic Angiography: A Retrospective Cohort Study. Issue 16 (20th August 2019) - Dahl, Lindsey; Schultz, Annette; McGibbon, Elizabeth; Brownlie, Jarvis; Cook, Catherine; Elbarouni, Basem; Katz, Alan; Nguyen, Thang; Sawatzky, Jo Ann; Sinclaire, Moneca; Throndson, Karen; Prior, Heather J.; et al.
Abstract : Background: In Canada, First Nations (FN) people are at greater risk of mortality than the general population following index angiography. This disparity has not been investigated while considering guideline‐recommended cardiovascular medication use. Methods and Results: Retrospective analysis of administrative health data investigated patterns of medication dispensation during the first year after index angiography among patients in Manitoba, Canada. Medication possession ratios (MPRs) reflecting the percentage of days in which medications were supplied were calculated separately for β‐blockers, angiotensin‐converting enzyme inhibitors, statins, and antiplatelets (clopidogrel). Patients were assigned to 1 of 4 categories: (1) not dispensed (0% MPR), (2) low (1–39% MPR), (3) intermediate (40–79% MPR), (4) high (≥80% MPR). Cox regression models that adjusted for MPR categories were used to explore the association between FN patients and both 5‐year all‐cause mortality and cardiovascular mortality. FN patients were less likely to have an intermediate MPR (odds ratio: 0.75; 95% CI, 0.57–0.99) or a high MPR (odds ratio: 0.64; 95% CI, 0.50–0.81) for statin medications than non‐FN patients. FN patients also had higher adjusted risks of all‐cause and cardiovascular mortality than non‐FN patients (hazard ratio, all‐cause: 1.54 [95% CI, 1.25–1.89]; cardiovascular: 1.62 [95% CI, 1.16–2.25]). Conclusions: FN status was independently associated with intermediate and high MPRs for statins during the first year following index angiography among patients with known ischemic heart disease. Differences in MPR categories did not explain the disparity in all‐cause and cardiovascular mortality between the 2 populations. Reduction of cardiovascular disparities may be best addressed using primary prevention strategies that include decolonizing policies and practices.